PELATIHAN PENGENALAN E-COMMERCE BAGI PELAKU UMKM DI DESA JAYAGIRI KECAMATAN LEMBANG BANDUNG BARAT - Agus Kusmana; Syarif Ali (Gapenas Publisher, 2022)
Jayagiri Village, Lembang District, is located in the government area of ??West Bandung Regency. Most of the population in Jayagiri Village work as employees, laborers, entrepreneurs, employees and farming. For potential commodities in this area, there are several home industries as well as in the field of agribusiness. One of the agricultural commodities found in this area is the Jayagiri Coffee product which is ready to be consumed or ready to serve anytime anywhere. The development of information technology is very rapid. One example is the development of the internet, its existence has an influence on SMEs. related to the world of business or business. In addition to simplifying and accelerating the process of communication and information, information technology has many conveniences and functions from the use of digital media, encouraging the public or entrepreneurs to take advantage of the digital media in every activity. Other functions of using digital media include: branding, sharing, promotion, and marketing. Based on this reality, efforts to overcome problems in terms of marketing for MSMEs of Jayagiri Coffee. The next stage is to prepare so that MSME actors can be independent and can create webbs and understand E-commerce. This is done by providing training and guidance on on-line marketing and understanding about online marketing in the digital era and monitoring and mentoring